CRYSTALLINE AND DIGESTIVE CHARACTERISTICS OF HEAT MOISTURE TREATED AND ANNEALED LESSER YAM (Dioscorea esculenta) STARCH - Laksmi Putri Ayuningtyas; Ashri Mukti Benita; Desy Triastuti (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2022)
Hydrothermal modification is a physically safe modification applied in a food product to enhance its functional properties and to extend the starch application in the food industry. Heat Moisture Treatment (HMT) and Annealing (ANN) affect the starch’s functional properties in its crystalline and digestive characteristics. Native starch is modified by HMT with 25% moisture content and 4 hours heating time, by ANN with starch and water ratio of 1:3 (w/w), and 10 hours at 50°C. Modified lesser yam starch by HMT and ANN have different crystalline and digestive characteristics from its native, although the modification do not change its granule morphology. The diffraction pattern of HMT starch is changed from A-type to A+B-type, but not on the ANN starch. Starch content and digestive value decreased, while amylose and resistant starch content increased compared to native starch. Hydrothermally modified starch could be considered as a raw material in thermally stable functional foods.